Plant Metabolism Methods and Protocols - Sriram, Ganesh; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
In Plant Metabolism: Methods and Protocols, expert researchers in the field present the latest methods on quantitative analysis of plant metabolism. The methods focus on measurements, analyses and simulations of molecules, fluxes, and ultimately entire metabolic pathways and networks. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials, reagents, or software, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Plant Metabolism: Methods and Protocols seeks to benefit scientists ranging from plant biology, metabolic engineering, and biotechnology.
MeRy-B, a Metabolomic Database and Knowledge Base for Exploring Plant Primary Metabolism -- Targeted Deuteration of Polyphenolics for their Qualitative and Quantitative Metabolomic Analysis in Plant-Derived Extracts -- Relative Quantitation in Single Cell Metabolomics by Laser Ablation Electrospray Mass Spectrometry -- Quantification of Plant Volatiles -- Quantitative Imaging Approaches for Small Molecule Measurements using FRET Sensors in Plants -- Isotopomer Measurement Techniques in Metabolic Flux Analysis I: Nuclear Magnetic Resonance -- Isotopomer Measurement Techniques in Metabolic Flux Analysis II: Mass Spectrometry -- Mathematical Modeling of Isotope Labeling Experiments for Metabolic Flux Analysis -- Optimal Design of Isotope Labeling Experiments -- Putting the Plant Metabolic Network Pathway Databases to Work: Going Offline to Gain New Capabilities --  Elucidation of Metabolic Pathways from Enzyme Classification Data --  Deducing Intracellular Distributions of Metabolic Pathways from Genomic Data -- Genome-scale Models of Plant Metabolism -- Elementary Flux Modes, Flux Balance Analysis and their Application to Plant Metabolism Junker -- Systems Approaches to Unraveling Plant Metabolism: Identifying Biosynthetic Genes of Secondary Metabolic Pathways -- Applications of Kinetic Modeling to Plant Metabolism -- Kinetic Modeling of Plant Metabolism and its Predictive Power – Peppermint Essential Oil Biosynthesis as an Example.
Keywords: Plant science; Botany; Plant biochemistry; Metabolism; Plant Sciences; Plant Biochemistry; Metabolomics